Clinical Features of Urticaria: Results From a Hospital-Based Multicenter Study in China - Wang, Xin; Liu, Li-Juan; Li, Lin-feng; Shi, Xiao-Dong; Shen, Yi-Wei (Frontiers in Medicine, 2022)
Background The clinical features of urticaria have not been fully illustrated. Objectives To demonstrate clinical features of urticaria in different areas of southern and northern China. Methods In this hospital-based multicenter study, outpatients with urticaria filled in a questionnaire during the initial visit and follow-up (once per week, lasting for a month). Results Overall, 1,715 outpatients with urticaria with a mean age of 37.86 ± 16.08 years (range = 0.5–87 years) were recruited. The median disease duration was 1.94 ± 4.31 years (range = 0–58 years). More itching was observed in the northern areas higher than that in the southern areas (99.5 vs 94.1%, P < 0.001). The incidence of pain, arthralgia, and family history in southern areas was higher than that in northern areas (5.1 vs 1.1%, 9.6 vs 0, 10.6% vs 3.2%, P < 0.001). The leading subtypes of specified urticaria were chronic spontaneous urticaria (81.4%) and symptomatic dermographism (35.9%). The incidence of symptomatic dermographism and cold urticaria in the southern areas was lower than that in the northern areas (31.8 vs. 50.3%, 4 vs. 8.5%, P < 0.001). Allergic diseases were the most common concomitant disorders of urticaria. More than half of the patients had to avoid certain food, such as fish-prawn-crab (30.7%) and alcohol (20%). Ebastine (41.1%) was the most commonly prescribed drug. The disease duration negatively correlated with the severity of itching and number of wheals (>50/24H) (Spearman’s rank correlation test, p < 0.001). Conclusion This study provides a profile of clinical characteristics of urticaria in China and filled the gap in the field of regional comparative studies on urticaria.